SINTESIS BIODIESEL DARI CRUDE PALM OIL DENGAN KATALIS ALUMINA HASIL RECOVERY LIMBAH PADAT LUMPUR PDAM INTAN BANJAR - Doni Rahmat Wicakso (INFO-TEKNIK, 2011)
The purposed of this research is to prove the ability of alumina which is obtained from PDAM sludge waste as a catalyst in biodiesel syntetic from crude palm oil and to get the optimum additions of alumina catalyst and the optimum temperature of process. Alumina catalyst is a heterogeneous catalyst or a catalyst which is consisting in solid phase. The advantage of this alumina catalyst is its ability to recovered, reusable, and simple in its separation process, because the soluble product in reaction medium could be separated from its catalyst by filtration. Alumina was obtained from PDAM sludge waste by adding NaOH, NH4Cl, and NH4OH in it, then heat at 90oC for 2,5 hours,  filtrated, and dried in the oven. Esterification process works by heating methanol, H2SO4, and CPO at 60oC by comparison of CPO and methanol 1:6 in moles. Continued with transesterification process by temperature variations of 40oC, 50oC, 60oC, and 70oC, also alumina catalyst variations of 3%-b, 4%-b, and 5%-b. After esterification-transesterifications process, we purified crude biodiesel by wash it with aqudest to make pure crude biodiesel.Optimum temperature in this research about 60oC with optimum catalyst about 5%. It was  reasoned by optimum yield we obtained about 70,5%.